2018
DOI: 10.1002/2017gl076817
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Representativeness Error in the Ground‐Level Observation Networks for Black Carbon Radiation Absorption

Abstract: There is high uncertainty in the direct radiative forcing of black carbon (BC), an aerosol that strongly absorbs solar radiation. The observation‐constrained estimate, which is several times larger than the bottom‐up estimate, is influenced by the spatial representativeness error due to the mesoscale inhomogeneity of the aerosol fields and the relatively low resolution of global chemistry‐transport models. Here we evaluated the spatial representativeness error for two widely used observational networks (AEroso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 46 publications
(96 reference statements)
1
32
0
Order By: Relevance
“…With added information of their sky radiances samples, the AERONET Sun photometers also provide information on vertically integrated aerosol size and light absorption. However, continental and often near‐urban locations lead to systematic biases (R. Wang et al, ). To supplement these measurements, long‐term satellite remote sensing retrievals are also available, with more than 30 years of passive measurements, including almost two decades of Moderate Resolution Imaging Spectroradiometer (MODIS) aerosol retrievals; and more than a decade of active measurements using the Cloud‐Aerosol Lidar with Orthogonal Polarization (CALIOP).…”
Section: Preindustrial To Present‐day Change In Aodmentioning
confidence: 99%
“…With added information of their sky radiances samples, the AERONET Sun photometers also provide information on vertically integrated aerosol size and light absorption. However, continental and often near‐urban locations lead to systematic biases (R. Wang et al, ). To supplement these measurements, long‐term satellite remote sensing retrievals are also available, with more than 30 years of passive measurements, including almost two decades of Moderate Resolution Imaging Spectroradiometer (MODIS) aerosol retrievals; and more than a decade of active measurements using the Cloud‐Aerosol Lidar with Orthogonal Polarization (CALIOP).…”
Section: Preindustrial To Present‐day Change In Aodmentioning
confidence: 99%
“…The sea salt module originally introduced by Grini et al (2002) has been updated with a new production parameterization following recommendations by Witek et al (2016). Using satellite retrievals, Witek et al (2016) evaluated different sea spray aerosol emission parametrizations and found the best agreement with the emission function from Sofiev et al (2011) including the sea surface temperature adjustment from Jaeglé et al (2011). Compared to the previous scheme, the global production of sea salt is reduced, while there is an increase in the tropics.…”
Section: Oslo Ctm3mentioning
confidence: 99%
“…Despite the tremendous efforts (Huang, Fu, et al, 2015;Huang, Song, et al, 2015;Qi et al, 2017;Samset & Myhre, 2015;Tosca et al, 2013), significant uncertainty remains in the estimation of BC direct forcing (R. Wang et al, 2018). DRE describes the instantaneous influence of BC on the atmospheric energy balance while DRF is calculated as the change of DRE from preindustrial to present day.…”
Section: Introductionmentioning
confidence: 99%
“…DRE describes the instantaneous influence of BC on the atmospheric energy balance while DRF is calculated as the change of DRE from preindustrial to present day. Despite the tremendous efforts (Huang, Fu, et al, 2015;Huang, Song, et al, 2015;Qi et al, 2017;Samset & Myhre, 2015;Tosca et al, 2013), significant uncertainty remains in the estimation of BC direct forcing (R. Wang et al, 2018). Phase I of the Aerosol Model Comparison Project (Schulz et al, 2006) reported global mean BC DRF between 1750 and 2000 as 0.25 W/m 2 with a range of 0.08 to 0.36 W/m 2 .…”
Section: Introductionmentioning
confidence: 99%